2011
DOI: 10.1002/etc.741
|View full text |Cite|
|
Sign up to set email alerts
|

Detection of retinoic acid receptor agonistic activity and identification of causative compounds in municipal wastewater treatment plants in Japan

Abstract: Retinoic acid (RA) receptor (RAR) agonists are potential toxicants that can cause teratogenesis in vertebrates. To determine the occurrence of RAR agonists in municipal wastewater treatment plants (WWTPs), we examined the RARα agonistic activities of influent and effluent samples from several municipal WWTPs in Osaka, Japan, using a yeast two-hybrid assay. Significant RARα agonistic activity was detected in all the influent samples investigated, suggesting that municipal wastewater consistently contains RAR ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
3
8
0
Order By: Relevance
“…Retinoids control vertebrate morphogenesis, growth, cellular differentiation, and tissue homeostasis, and an imbalance of retinoids and related substances can induce teratogenic effects in amphibians and fish . Retinoid acid receptor α (RARα) activity was frequently detected in (un)­treated wastewater and surface waters. , Compared to that, retinoid X receptor (RXR) activity is less common. , Nevertheless, RARα activity in conventionally treated wastewater is mostly low or below the LOD due to the effective removal by CT. ,, Three studies investigated retinoid-like activity during advanced wastewater treatment in five assays. ,, The first study reported no activity above the LOD for the RXR and RARα . In contrast, Cao et al observed a very effective reduction of RARα activity by ozonation, even at a low ozone dose of 2 mg L –1 .…”
Section: Removal Of In Vitro Toxicitymentioning
confidence: 99%
“…Retinoids control vertebrate morphogenesis, growth, cellular differentiation, and tissue homeostasis, and an imbalance of retinoids and related substances can induce teratogenic effects in amphibians and fish . Retinoid acid receptor α (RARα) activity was frequently detected in (un)­treated wastewater and surface waters. , Compared to that, retinoid X receptor (RXR) activity is less common. , Nevertheless, RARα activity in conventionally treated wastewater is mostly low or below the LOD due to the effective removal by CT. ,, Three studies investigated retinoid-like activity during advanced wastewater treatment in five assays. ,, The first study reported no activity above the LOD for the RXR and RARα . In contrast, Cao et al observed a very effective reduction of RARα activity by ozonation, even at a low ozone dose of 2 mg L –1 .…”
Section: Removal Of In Vitro Toxicitymentioning
confidence: 99%
“…Humans, as well as animals, excrete retinoids most often as 4-oxo derivatives [277][278][279]. Even though retinoids are sensitive to oxidation and isomerization processes that significantly alter their bioactivity, in municipal wastewater treatment plants the treatment efficiency may not be sufficient for their complete removal and, consequently, retinoids can be released to the receiving water bodies at concentrations of up to 11.5 ng REQ × L −1 [253,271,[280][281][282][283]. Amongst the detected isomers, oxidized (i.e.…”
Section: European and Asian Environmental Case Examplesmentioning
confidence: 99%
“…RAs and their oxidative metabolites 4-oxo-RAs could be eliminated from humans and wildlife through urinary excretion, as well as used as RA-containing drugs for treating skin and blood diseases . As a result, RAs and 4-oxo-RAs are commonly found in effluents of sewage treatment plants (STPs), which would be a source of RAs and 4-oxo-RAs into aquatic environments. Nevertheless, these chemicals usually showed relatively low levels in seawater.…”
Section: Introductionmentioning
confidence: 99%